Polymer melt rheology: Advantages of frequency sweeps using randomly selected frequencies. Issue 2 (13th August 2021) - Shaw, Montgomery T.
Abstract: Measurement of the viscoelastic properties of polymer solids, melts, and solutions is broadly practiced. The so‐called "frequency sweep" appears in thousands of publications, with data covering up to five decades of frequency to reveal, for example, the relative molecular size of a polymer. To perform these experiments, the frequency range is typically "swept" from high to low frequency or vice versa. Unfortunately, this confounds frequency with run time. This is more than annoying; time effects can result in serious mistakes in the interpretation of the data. Fortunately, the confounding can be eliminated by simply running the frequencies in random order, which converts the time trend to random error. Described here is how this can be done and shows via modeling that the result can not only show that time effects are present but can be analyzed to show the time rate of change of the sample. This analysis is demonstrated using two real examples: loss of solvent from poly(dimethyl siloxane) gum and gelation of porcine gelatin. This method compares well with the multiwave technique, but does not require any special software or adjustments of amplitude with frequency or harmonic spacing of the frequencies. Abstract :